IDENTIFICATION OF -2849 IL-10 GENE PROMOTER POLYMORPHISM IN LEPROSY PATIENT - Desi Oktariana; Arina P Jatmiko; Mutiara Budi Azhar (JURNAL KEDOKTERAN DAN KESEHATAN, 2022)
Leprosy is a chronic granulomatous disease. Leprosy is caused by M. leprae. However, not all exposure to M. leprae causes the disease. The condition of the host immune system determines the pathogenesis of leprosy. Interleukin-10 work as a pro- and anti-inflammatory cytokine. Polymorphism in the IL-10 gene promoter affects the amount of IL-10 secretion. The amount of IL-10 secretion determines the body’s response to M. leprae. The purpose of this study was to determine the distribution of -2849 IL-10 gene promoter polymorphism in leprosy patient at RSUP dr. Mohammad Hoesin Palembang. This research is an observational descriptive study with cross sectional design. Polymorphism identification was performed using PCR-RFLP. A total of 50 samples were identified. Most of the leprosy patients at RSUP dr. Mohammad Hoesin for the period January – February were < 50 years old (73.47%), male (66%), MB leprosy (92%), and came from Malay-South Sumatra ethnicity (53.06%). The genotype frequency distribution was GG 93.88%, AG 6.12%, and AA 0%. The frequency of allele G was 96.94% and allele A 3.06%. The majority of leprosy patients at RSUP dr. Mohammad Hoesin had wild-type genotypes.